The Rise and Development of Public Health Communication. Issue 13 (9th November 2020) - Salmon, Charles T.; Poorisat, Thanomwong
ABSTRACT: Public health communication as a socio-cultural practice can trace its lineage to the dawn of human civilization and the earliest attempts to warn, educate and influence behaviors of individuals and communities facing public health problems. But public health communication in the sense that it is understood today required contemporaneous advancement and innovations in the allied disciplines of public health and social sciences as well as in the communication industries. This essay reviews a largely forgotten history of public health communication that coincides with the onset of the "modern era" of public health in the late 1800s and continues through the 1960s. Four key developments are identified as influential in the evolution of what eventually would come to be known as public health communication: (1) the early use of mass communication for public health campaigns, (2) the search for effects, (3) the search for explanation from interdisciplinary perspectives, and (4) the formal recognition of health communication as a distinct and valuable field of practice and research.